Forensic science detection of composite photographs - Cern, Wong Vic (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
Photograph that is suspected to be forged one is occasionally encountered by the forensic practitioner for identification. This kind of examination is one of the most challenging problems in forensic photography. This identification is dependent on the existence of certain characteristics like inconsistencies in magnification, contrast and perspective. The study is intended to probe further into the salient features of photograph that can be used to identify a composite/forged photograph. The study is limited to composite/forged photograph produced by conventional montage techniques. Photography experiments demonstrating the variation as a result of changes in focal length, aperture (f-stop number), object distance, lighting, shadow formations and film ISO film rating are performed. Important features that could be used in the identification of a composite/forged photograph were documented. A questioned photograph has been produced with photomontage technique. This questioned photograph is forensically examined and identified as forged a one.